Haydar Ergülen - Ayşe Saraçgil (Lea, 2014)
In the following lines there is a brief biography of the Turkish poet Haydar Ergülen who came to prominence in the 1980s together with some information on his poetry, which is considered as part of the poetics began by the components of the so-called movement of İkinci yeni (Second New), which in the 1950s revolutionized Turkish poetics as established during the first decades of the Republican period. This biography is meant to be an introduction to the first translation of four of his poems in Italian.